Internship report at Human Resource Management: Faculty of Business Management / Muhammad Shaiful Haslim Baharudin - Baharudin, Muhammad Shaiful Haslim (Universiti Teknologi MARA, Perlis, 2024)
This report was developed to document comments and personal reflections on the location of my training. The PESTEL analysis framework is used to conduct the SWOT analysis. The primary goal of this report is to assess my understanding of the sector as part of a reflective journey on what was accomplished throughout the 24-week internship.